The effect of different types of filler on the mechanical and physical properties of wood plastic composite from eucalyptus spp / Noorshashillawati Azura Mohammad...[et al.] - Mohammad, Noorshashillawati Azura; Sarmin, Siti Noorbaini; Mohd Hassan, Nurul Husna; Mahmud, Siti Zalifah; Ahmad, Nurrohana; Mohd Akil, Fatma Adhira Shafiqa (Universiti Teknologi MARA Cawangan Pahang, 2019)
Nowadays with increasing environmental concerns, many researchers start using biocomposites such as wood fiber, bamboo, sisal, hemp and flax for composites manufacturing. Generally, wood plastic composites (WPCs) have gained interest in commercial markets for automobile (interior panels, trunk liners, spare tire covers, and package trays) and construction (deck boards, stairs, post sleeves, and hand rails) fields. WPC needs lower maintenance than the alternatives of solid wood treated with preservatives or solid wood of rot-resistant species and claimed as more environmentally friendly by manufacturers. Since it can performs like conventional wood, it does not require special fasteners and design changes in application. In this study, our attempt for development of WPCs is focused on using wood fibers (Eucalyptus sp.) with polypropylene. Polypropylene is used, as it has high melting point of 170 °C and its mechanical properties are constant at ambient temperature. It also has dimensional consistency, impact resistance and high strength-to-weight ratios. Two types of fillers (virgin and recycled polypropylene) and three types of filler loadings (10%, 30% and 50%) were used for compounding with wood fibers. In addition, recycled polypropylene is used instead of recycled ethylene because of the availability of virgin polypropylene supplies in study area. Recycled polypropylene can be easily obtained from broken plastic buckets, basins, bottles and others.